Versatile Nanostructured Materials via Direct Reaction of Functionalized Catechols. (15th February 2013) - Saiz‐Poseu, Javier; Sedó, Josep; García, Beatriz; Benaiges, Cristina; Parella, Teo; Alibés, Ramon; Hernando, Jordi; Busqué, Felix; Ruiz‐Molina, Daniel
<x xml:space="preserve">Abstract</x> A facile one‐step polymerization strategy is explored to achieve novel catechol‐based materials. Depending on the functionality of the catechol, the as‐prepared product can be used to modify at will the surface tension of nano and bulk structures, from oleo‐/hydrophobic to highly hydrophilic. A hydrophobic catechol prepared thus polymerized shows the ability to self‐assemble as solid nanoparticles with sticky properties in polar solvent media. Such a versatile concept is ideal for the development of catechol‐based multifunctional materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>